Vagococcus fluvialis as a causative pathogen of bloodstream and decubitus ulcer infection: Case report and systematic review of the literature. Issue 2 (February 2021) - Matsuo, Takahiro; Mori, Nobuyoshi; Kawai, Fujimi; Sakurai, Aki; Toyoda, Makoto; Mikami, Yumiko; Uehara, Yuki; Furukawa, Keiichi
Abstract: Background: Vagococcal infections are uncommon in humans; there are limited studies on the clinical manifestations, the optimal methods for identifications, and antimicrobial susceptibility testing for vagococcal infections. Here, we have reported a case of Vagococcus fluvialis -induced bacteremia and decubitus ulcer and have systematically reviewed other reported Vagococcus infections. Case presentation: A 74-year-old man presented to our emergency department with muscle weakness on his left extremities, dysarthria, and altered mental status along with fever for the past 4 days. Physical examination revealed a decubitus ulcer with foul smelling and yellowish exudative pus on his left chest wall and abdomen, forearm, thigh, and lower leg. He was empirically treated with 2.25 mg of piperacillin/tazobactam every 8 hours and 0.5 g of vancomycin every 24 hours intravenously (IV) for his decubitus ulcer. Vagococcus fluvialis was detected in both aerobic and anaerobic blood cultures (upon admission) using the VITEC 2 GP ID card (bioMérieux) and matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) . We continued the mentioned IV antimicrobial therapies for 4 weeks following which the patient was transferred to a long-term care facility for further rehabilitation. Conclusions: To our best knowledge, this is the first literature review of Vagococcus infections in humans. Since it is challenging to distinguish Vagococcus from Enterococcus by a conventional method due to the similarity of its biochemical properties to those of Enterococcus, based on our literature review, 16S rRNA sequencing or analysis of bacterial protein profile using MALDI-TOF MS may be useful for the precise identification.